CTA seminar on regional small-scale fisheries improvement - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
CTA organized a seminar, jointly with CEASM and TDRI, on the improvement of fish products (preservation and processing) and the development of small-scale fishing in West-Africa which took place in Dakar from November 3 to 21. The seminar was...